Health Promotion Through Audio Visual and Simulation Effectively Reduces Children's Anxiety Due to Hospitalization - Fadlilah, Siti; Damayanti, Santi; Wijayanthi, Rachma Sukma; Widayati, Ririn Wahyu (Universitas Aisyah Pringsewu, 2022)
Preschool-aged children who are hospitalized are prone to anxiety. This anxiety, if not treated, can hinder the treatment process, and the length of treatment will increase. This study aims to determine the effect of health promotion using audio-visual media and simulations on the anxiety of hospitalized children in Mimika, Papua, Indonesia. The research used a quasi-experimental with a pretest-posttest control group. The sample used the control and intervention groups with 24 people in each group, the sampling technique used consecutive sampling. The instruments used were animated videos about medical devices and procedures, medical devices for simulation, standard operating procedures, observation sheets, and the Modified Yale Preoperative Anxiety Scale (mYPAS) anxiety questionnaire. Bivariate analysis is Paired T-Test and Independent T-Test: The intervention group decreased the average posttest anxiety score more than the control group (30.0 more than 5.4). Bivariate test between gender and age with anxiety showed p less than 0.05. The pretest-posttest comparison in the control and intervention groups was p=0.343 and p=0.000. At the same time, the comparison of posttest between the control and intervention groups showed p=0.002. Age and gender are related to the anxiety of pediatric patients. Health promotion and simulation of health tools and measures effectively reduce anxiety in pediatric patients.Abstrak: Anak usia prasekolah yang dirawat di rumah sakit rentan terhadap kecemasan. Kecemasan ini jika tidak diobati dapat menghambat proses pengobatan, dan lamanya pengobatan akan bertambah. Penelitian ini bertujuan untuk mengetahui pengaruh promosi kesehatan menggunakan media audio visual dan simulasi terhadap kecemasan anak rawat inap di Mimika, Papua, Indonesia. Penelitian menggunakan eksperimen semu dengan pretest-posttest control group. Sampel menggunakan kelompok kontrol dan intervensi dengan jumlah masing-masing 24 orang, teknik pengambilan sampel menggunakan consecutive sampling. Instrumen yang digunakan adalah video animasi tentang alat dan prosedur medis, alat simulasi medis, prosedur operasi standar, lembar observasi, dan kuesioner kecemasan Modified Yale Preoperative Anxiety Scale (mYPAS). Analisis bivariat adalah Paired T-Test dan Independent T-Test: Kelompok intervensi mengalami penurunan rata-rata skor kecemasan posttest lebih besar dibandingkan kelompok kontrol (30,0 lebih dari 5.4). Uji bivariat antara jenis kelamin dan usia dengan kecemasan menunjukkan p kurang dari 0,05. Perbandingan pretest-posttest pada kelompok kontrol dan intervensi adalah p=0,343 dan p=0,000. Sementara itu, perbandingan posttest antara kelompok kontrol dan intervensi menunjukkan p=0,002. Usia dan jenis kelamin berhubungan dengan kecemasan pasien anak. Promosi kesehatan dan simulasi alat dan tindakan kesehatan secara efektif mengurangi kecemasan pada pasien anak.